   Chapter 6.3, Problem 39ES ### Discrete Mathematics With Applicat...

5th Edition
EPP + 1 other
ISBN: 9781337694193

#### Solutions

Chapter
Section ### Discrete Mathematics With Applicat...

5th Edition
EPP + 1 other
ISBN: 9781337694193
Textbook Problem
1 views

# In 30-40, construct an algebraic proof for the given statement, Cite a property from Theorem 6,2,2 for every step.For all sets A and B, ( A − B ) ∪ ( B − A ) = ( A ∪ B ) − ( A ∩ B ) .

To determine

To prove:

(AB)(BA)=(AB)(AB)

Explanation

Given information

(AB)C=(AC)(BC)

Concept used:

(AB)C=(AC)(BC)

Cite a property from Theorem 6.2.2 for every step of the proof.

Solution let A,B and C be any sets. Then

(AB)C=(AB)Cc                  by the set difference law=Cc(AB)                  by the commutative law for =(CcA)(CcB)      by the distributive law=(ACc)(BCc)      by the commutative law for =(AB)(BC)          by the set difference law

Calculation:

(AB)(BA)=(ABc)(BAc)                                             by set difference ={A(B<

### Still sussing out bartleby?

Check out a sample textbook solution.

See a sample solution

#### The Solution to Your Study Problems

Bartleby provides explanations to thousands of textbook problems written by our experts, many with advanced degrees!

Get Started 